2014
DOI: 10.4236/oalib.1100997
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Intimate Partner Violence during Pregnancy among Recently Delivered Women in Public Health Facilities of Hossana Town, Hadiya Zone, Southern Ethiopia

Abstract: Background: Intimate partner violence is recognized as a worldwide serious public health problem. It can cause serious injury, disability or death. Risk factors for intimate partner violence during pregnancy are often similar to risk factors for intimate partner violence in general. Objectives: To assess the prevalence and associated factors of intimate partner violence during pregnancy among recently delivered women in public health facilities of Hossana Town, Hadiya Zone, Southern Ethiopia, 2014. Methods: Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
25
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 9 publications
(9 reference statements)
9
25
5
Order By: Relevance
“…In our study, the final adjusted multivariable analysis model for factors associated with lifetime IPV showed that none of the socio-demographic variables is statistically significant. This finding contrasts with other studies which have reported IPV related to low educational status of women (Onigbogi et al 2015) and the husbands/partners (Al Serkal et al 2014;Laelago et al 2014), and low socio-economic status of the family (Abeye et al 2011). The current study did not find any significant relationships between educational level and income level with women's experience of lifetime and past-year IPV.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the final adjusted multivariable analysis model for factors associated with lifetime IPV showed that none of the socio-demographic variables is statistically significant. This finding contrasts with other studies which have reported IPV related to low educational status of women (Onigbogi et al 2015) and the husbands/partners (Al Serkal et al 2014;Laelago et al 2014), and low socio-economic status of the family (Abeye et al 2011). The current study did not find any significant relationships between educational level and income level with women's experience of lifetime and past-year IPV.…”
Section: Discussioncontrasting
confidence: 99%
“…The most common types of emotional violence exerted by the intimate partner in the present study included words or actions that scared or intimidated the woman on purpose, followed by insulting the woman or making the woman feel bad about herself. This is in accordance with previous studies reporting insult and humiliation as the most common types of emotional violence [ 38 – 40 ]. Hence, from a public health perspective this emphasizes the importance of increasing the focus on emotional violence due to its high prevalence and the associated psychological distress, which may result in adverse health outcomes, including mental distress and negative pregnancy related health outcomes [ 41 ].…”
Section: Discussionsupporting
confidence: 94%
“…Regarding individual related factors, this study confirmed that violence foster violence and witnessing IPV in childhood increases the likelihood of violent behaviour in the next generation [ 13 , 23 , 40 , 42 , 48 ]. Partner’s use of substance/s (alcohol, Khat, and/smoking), is a known and significant factor of IPV during pregnancy [ 4 , 13 , 14 , 23 , 40 , 49 52 ], and enhancing if the partner also has mental health or personality problems [ 40 , 53 ]. Factor related to the indivdual domain is the strongest in this model ( Table 3 ), but with wide confidence intervals.…”
Section: Discussionmentioning
confidence: 99%